2012
DOI: 10.3892/br.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Screening for specific biomarkers in the serum of postmenopausal osteoporosis patients using proteomic fingerprint techniques

Abstract: Abstract. The aim of this study was to detect serum protein biomarkers and establish a diagnostic model for postmenopausal osteoporosis (PMOP) adopting matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) combined with weak cationic exchange (WCX) magnetic beads, and to study the clinical significance of the model in the early diagnosis of PMOP. Serum samples from 45 patients with PMOP, 30 patients with osteopenia and 40 healthy controls were prepared using WCX magnetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similar to the findings of Fietta et al using BALF of patients with SSc-ILD (19), calgranulin B was also increased in ILD patients with myositis overlap syndrome. Studies have shown that calgranulin B plays a role in endothelial inflammation and participates in the recruitment of white blood cells to the inflammatory site (55,56), and its expression is related to the inflammatory activity of systemic vasculitis (57). These findings suggest that there may be a common pathological pathway among different CTD-ILD subtypes, but the role of various proteins needs further classification research.…”
Section: Proteomics Studies In Idiopathic Inflammatory Myopathiesmentioning
confidence: 99%
“…Similar to the findings of Fietta et al using BALF of patients with SSc-ILD (19), calgranulin B was also increased in ILD patients with myositis overlap syndrome. Studies have shown that calgranulin B plays a role in endothelial inflammation and participates in the recruitment of white blood cells to the inflammatory site (55,56), and its expression is related to the inflammatory activity of systemic vasculitis (57). These findings suggest that there may be a common pathological pathway among different CTD-ILD subtypes, but the role of various proteins needs further classification research.…”
Section: Proteomics Studies In Idiopathic Inflammatory Myopathiesmentioning
confidence: 99%
“…Several types have been described in the literature; some with porous structure to specifically retain target analytes, for example restricted access materials (RAM) or molecular imprinted polymers (MIP); others with very specific functional groups (e.g. immunosorbents), or unspecific materials such as non‐polar coatings (C8, C18,…), ion exchange groups, or moieties that provide aromatic interactions. The extraction procedure is similar to solid‐phase extraction (SPE); i.e., loading, washing, and elution, with the added advantage that the suspended magnetic beads can be handled as a liquid.…”
Section: Introductionmentioning
confidence: 99%